Sharon Dunwoody's Legacy: Three Timely Lessons for Us. Issue 1 (February 2023) - Peters, Hans Peter
Sharon Dunwoody gained international reputation for her research on science journalism and media risk communication. Drawing on her publications published over more than four decades and the author's long-lasting collaboration with her, this commentary elaborates on three of her most characteristic beliefs and orientations and suggests that they may serve as timely lessons for us to critically reflect on current assumptions and practices: substance over showmanship, improving one-way communication, and respecting the audience.